Actuating Soft Matter with Magnetic Torque. (6th April 2016) - Erb, Randall M.; Martin, Joshua J.; Soheilian, Rasam; Pan, Chunzhou; Barber, Jabulani R.
Abstract : Here, recent significant developments are reviewed in manipulating soft matter systems through the use of magnetic torque. Magnetic torque enables the orientation, assembly, and manipulation of thermally fluctuating systems in broad material fields including biomaterials, ceramic and composite precursor suspensions, polymer solutions, fluids, foams, and gels. Magnetism offers an effective, safe, and massively parallel manufacturing approach. By exploiting magnetic torque, leading soft matter researchers have demonstrated new technologies in rheology, life sciences, optics, and structural materials. Specifically, magnetic torque has been used to assemble particle suspensions, to fabricate and actuate composite materials, and to control and manipulate biological materials. In each of these applications, there are energetic limitations to magnetic torque that need to be understood and characterized. However, magnetic torque offers a promising remote‐controlled approach to creating and enabling new soft matter technologies. Abstract : Breakthroughs in actuating soft matter with magnetic torque in three principal research directions are highlighted: controlling particle suspensions, actuating composite materials, and manipulating biomaterials. Progress in these fields has rich application in life sciences, microfluidics, rheology, and energy systems. An outlook is offered for the current challenges and opportunities in using magnetic torque as a manipulation and actuation strategy.